A Case of Von Hippel-Lindau Disease Presented with Multiple Pancreatic Cysts and Medullary Hemangioblastoma - Young Hyun Kim; Hye Lim Jung; Aram Yang; Ji Hee Kwak; Deok Soo Kim; Jung Yeon Shim; Jae Won Shim (The Korean Society of Pediatric Hematology-Oncology, 2020)
Von Hippel-Lindau (VHL) disease is a rare inherited cancer predisposition syndrome characterized by benign and malignant tumors in multiple organs, especially cerebellar hemangioblastomas, retinal angiomas, renal-cell carcinoma, and pheochromocytomas. Clinically, VHL disease also presents an increased risk for developing multiple visceral cysts in the pancreas, liver, and kidneys. Regular surveillance for VHL disease-associated tumors after early diagnosis is necessary for better outcomes in VHL disease. An 11-year-old girl was admitted with prolonged fever lasting for more than 10 days and cervical lymphadenopathy. She did not have a family history of cysts or malignancy. Initial blood tests showed mild leukopenia and moderate elevation in aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase, but with normal amylase and lipase. Hepatobiliary ultrasonography and magnetic resonance cholangiopancreatography were done and revealed multiple cysts involving the whole pancreas with cyst sizes up to 1.6 cm, indicating VHL disease. Direct sequencing of the VHL gene showed a heterozygous duplication at codon 384 (c.384dup), which is predicted to cause a frameshift of the reading frame (p.Leu129Serfs*3). This was a novel pathogenic variant VHL gene. We carried out the surveillance protocol for VHL disease-associated tumors, and found a hemangioblastoma in the medulla of the brainstem. We are reporting an 11-year-old female patient of VHL disease with brainstem hemangioblastoma who could be suspected and diagnosed of VHL disease in asymptomatic state due to incidentally found multiple pancreatic cysts.